Spatial Mobility Patterns of the Population of Alalak District and Their Implications for the Concentration of Urban Activities in Banjarmasin City - Eva Alviawati; Parida Angriani; Karunia Puji Hastuti; Nevy Farista Aristin (Universitas Lambung Mangkurat, 2026)
Population growth is always accompanied by increasing demands for living and space. Limited availability of space within the city gives rise to alternatives to meet the need for residential space, which involves taking up space in the suburbs. This study aims to analyze the spatial movement patterns of residents of Alalak District, a suburb of Banjarmasin, and to analyze the reasons driving population movement towards Banjarmasin, as well as its relationship to the concentration of activities in Banjarmasin. The study was conducted in Alalak District, Barito Kuala Regency, which is divided into three zones based on distance from Banjarmasin: Zone 1 (less than 10 km), Zone 2 (10-20 km), and Zone 3 (20-30 km). Data were obtained through structured interviews with 150 respondents. The results indicate that work activities, especially those of husbands, shopping for annual necessities and luxury goods, and college activities tend to be more concentrated in Banjarmasin. The reasons driving this movement pattern are related to the quality and quantity of services, as well as accessibility to Banjarmasin. The higher population movement to Banjarmasin, the greater the concentration of activities in Banjarmasin.